Incertaine Identité : Behind a cloudy sky. - Beecroft, Vanessa; Benning, Sadie; Cattelan, Maurizio; Collishaw, Mat; Emin, Tracey; Flanagan, Bob; Harris, Lyle Ashton; Herzog, Roland; Ladame, François; Lindell, John; Maffesoli, Michel; Marisaldi, Eva; et al. (Genève : Galerie Analix - B.& L. Polla, 1994)
Beecroft, Vanessa ; Benning, Sadie ; Cattelan, Maurizio ; Collishaw, Mat ; Flanagan, Bob ; Herzog, Roland ; Lindell, John ; Marisaldi, Sarah Lucas Eva ; Oppenheim, Kristin ; Vidya, Jean-Michel ; Wearing, Gillian ; Williams, Sue ; Arienti, Stefano ; Emin, Tracey ; Harris, Lyle Ashton ; Dunning, Jeanne ; Gonzales, Mark ; Martegani, Amedeo ; Pivi, Leonardo
Engels
Frans
boek